Prevalence, Genotype Distribution and Risk Factors of Human Papillomavirus in Moroccan Women - Khaali, Wafa; Gihbid, Amina; ElAmrani, Amal; Chaoui, Imane; Attaleb, Mohammed; Benhassou, Mustapha; Belghmi, Khalid; Mzibri, Mohammed El; Khyatti, Meriem (Archives of Clinical and Biomedical Research, 2019)
In Morocco, cervical cancer and precancerous lesions are still a public health problem and many efforts are made to improve women's awareness on Human papillomavirus (HPV) infection and methods preventing its dissemination. This study was planned to evaluate HPV prevalence and to assess the predominant HPV genotypes circulating in Morocco. A total of 360 women, attending caravans of sensitization and screening for cervical lesions were recruited from 9 different regions of Morocco. Socio-demographic, familial and medical data of participating women were recorded. HPV testing and genotyping were performed by Polymerase Chain Reaction and DNA direct sequencing. The overall HPV prevalence was 30.28% of the recruited women. Of the positive samples, 61.46% were infected with a high-risk HPV genotype, whereas 38.54% showed a low-risk HPV genotype. The most prevalent high-risk HPV genotypes were HPV 16, 59, and 18 with a prevalence of 25.68, 11.92 and 8.25%, respectively. Association between HPV infection and some potential risk factors was also assessed and showed a significant association with age, living environment (urban vs. rural) and familial status (p< 0.05). In conclusion, the present study clearly showed that HPV infection among Moroccan women is high, with a predominance of HPV 16 and 18, suggesting that the two available vaccines in Morocco, Gardasil and Cervarix, could be of a great interest to protect women against HPV infection and limit HPV dissemination in the whole country.